A convenient total synthesis of PSMA-617: A prostate specific membrane antigen (PSMA) ligand for prostate cancer endotherapeutic applications - K.S. Ajish Kumar; Anupam Mathur (Elsevier, 2022)
The treatment of metastatic Castration Resistant Prostate Cancer (mCRPC) by targeting Prostate Specific Membrane Antigen (PSMA), that is ubiquitously expressed on malicious cells, using177Lu-PSMA-617, has been showing great potential. Considering the promising results from Radioligand Therapy (RLT) studies conducted at multiple centres, 177Lu-PSMA-617, is being considered for FDA approval. The organic ligand, PSMA-617, is therefore in great demand, but it is also an expensive pharmaceutical precursor. We demonstrate here a convenient synthetic protocol for PSMA-617, using a solution phase method. Both, linear and convergent synthetic strategies were explored to affirm that the later approach furnished the target in better yield. The protocol presented here involves the use of commercially and economically viable reagents together with flow reactor based metal catalyzed hydrogenation as vital step. Using the method portrayed, PSMA-617 with purity >99.5% was achieved, while, radiolabelling with 177Lu afforded, 177Lu-PSMA-617 with radiochemical purity >98%, which is adequate for therapeutic applications. 177Lu-PSMA-617 prepared using the synthesized ligand showed parity in purity against that made from commercial equivalent.